Evaluation of antifungal activity of Magnesium oxide (MgO) and Iron oxide (FeO) nanoparticles on rot causing fungi - Koka, Jahangir Abdullah; Wani, Abdul Hamid; Bhat, Mohd Yaqub (Journal of Drug Delivery and Therapeutics, 2019)
The antifungal activity of Magnesium oxide (MgO) and iron oxide (FeO) nanoparticles prepared by bio safe method was evaluated for Penicillium expansum, Aspergillus niger, Alternaria alternata, Mucor plumbeus, Penicillium chrysogenum, Trichothecium roseum and Rhizoctonia solani. It was observed from the study that all the concentrations of nanoparticles brought about significant inhibition in the spore germination and mycelial growth of all the rot causing fungi. However, the highest inhibition in the germination of all the test fungi was observed at higher concentrations followed by lower concentrations of nanoparticles. It was observed from the present study that MgO and FeO nanoparticles showed signiﬁcant antimycotic activity against all the tested fungal pathogens. However, highest reduction in spore germination was observed against Mucor plumbeus whereas least reduction of spore germination was observed against Aspergillus niger at different concentration of nanoparticles of MgO respectively. Likewise, the maximum inhibition in the fungal growth was observed against Alternaria alternate and least inhibition in zone of fungal growth due to MgO nanoparticle was found against Mucor plumbeus respectively. Similarly, highest inhibition in spore germination was found against Penicillium expansum and least inhibition in spore germination was found against Aspergillus niger at different concentrations of nano FeO. Likewise, the maximum inhibition in the fungal growth was found against Rhizoctonia solani and Trichothecium roseum and least inhibition in zone of fungal growth was found against Penicillium expansum and Mucor plumbeus at 0.1mg/ml, 0.25mg/ml and 0.5 mg/ml concentrations of FeO nanoparticles respectively. Activity index was recorded highest against P. chrysogenum (0.97) in case of MgO and against T. roseum (0.97) in case of FeO nanoparticles respectively. Keywords: Spore germination, mycelial growth, rot causing fungi, tomato, brinjal, MgO and FeO nanoparticle